Comparative analysis of CAR T-cell therapy access for DLBCL patients: associated challenges and solutions in the four largest EU countries - Canales Albendea, Miguel Á.; Canonico, Pier Luigi; Cartron, Guillaume; Deiters, Barthold; Jommi, Claudio; Marks, Reinhard; Rioufol, Catherine; Sancho Cia, Juan M.; Santoro, Armando; Wagner-Drouet, Eva M. (Frontiers in Medicine, 2023)
CAR T-cell therapy has emerged as a promising new immuno-oncology treatment that engages the patient’s immune system to fight certain hematological malignancies, including diffuse large B-cell lymphoma (DLBCL). In the European Union (EU), CAR T-cell therapies have been approved for relapsed / refractory (R/R) DLBCL patients since 2018, but patient access is often still limited or delayed. In the ‘EU-4’ countries of France, Germany, Italy, and Spain, we calculated that in 2020, between 58% and 83% of R/R DLBCL patients (EMA approved label population) or between 29% and 71% of the estimated medically eligible R/R DLBCL patients, were not treated with a licensed CAR T-cell therapy. This study identifies common challenges along the patient journey that may result in limited access or delays to CAR T-cell therapy. These include timely identification and referral of eligible patients, pre-treatment funding approval by authorities and payers, and resource needs at CAR T-cell centers. These challenges, existing best practices and recommended focus areas for health systems are discussed here, with the aim to inform necessary actions for overcoming patient access challenges for current CAR T-cell therapies as well as for future cell and gene therapies.